2019
DOI: 10.3390/jcm8070948
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Apolipoprotein A-1 as Independent Predictors of Cardiovascular Mortality in Renal Transplant Recipients

Abstract: Renal transplant recipients (RTRs) are known to have a high cardio-vascular disease (CVD) burden only partly explained by traditional CVD risk factors. The aim of this paper was therefore to determine: i) the prognostic value of autoantibodies against apoA-1 (anti-apoA-1 IgG) for incidence of CVD mortality, all-cause mortality and graft failure in RTR. Four hundred and sixty two (462) prospectively included RTRs were followed for 7.0 years. Baseline anti-apoA-1 IgG were determined and associations with inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…Among autoantibodies of interest in CVD, the interest in antibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) appears to be gaining momentum. Indeed, three recent studies derived from a large multicenter general population cohort demonstrated that anti-ApoA-1 IgGs were an independent cardiovascular (CV) risk factor predictive of poor prognosis [3][4][5] similarly to what had been reported previously and more recently in high CV risk populations [6][7][8][9][10][11]. In parallel, translational studies pointed to these autoantibodies as mediators of atherogenesis, promoting atherosclerosis, myocardial necrosis, and mice death through toll-like receptors (TLR) 2,4 and CD14 signaling [12][13][14].…”
Section: Introductionsupporting
confidence: 71%
“…Among autoantibodies of interest in CVD, the interest in antibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) appears to be gaining momentum. Indeed, three recent studies derived from a large multicenter general population cohort demonstrated that anti-ApoA-1 IgGs were an independent cardiovascular (CV) risk factor predictive of poor prognosis [3][4][5] similarly to what had been reported previously and more recently in high CV risk populations [6][7][8][9][10][11]. In parallel, translational studies pointed to these autoantibodies as mediators of atherogenesis, promoting atherosclerosis, myocardial necrosis, and mice death through toll-like receptors (TLR) 2,4 and CD14 signaling [12][13][14].…”
Section: Introductionsupporting
confidence: 71%
“…Multivariate HRs were calculated after adjusting for age, gender, hypertension, diabetes, smoking, BMI, eGFR, HDL and LDL cholesterol, baseline CVD, and ADs. Humoral autoimmunity against apoA1 being known to be relevant for CVD, 2,3,5,8,10,11 sensitivity analyses were performed in primary and secondary prevention subgroups. Secondary prevention individuals were defined by the anamnestic presence of any CAD, any stroke or peripheral artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Routine analyses consisted of standard lipid profile, serum creatinine, glucose, homocysteine, uric acid, US-CRP, interleukin (IL)-1b, IL-6 and TNF-a measures that were performed according to routine methods as previously reported. 31,32 Anti-apoA1 and anti-cter apoA1 IgGs were measured following our validated anti-apoA1 IgG protocol reported above, [2][3][4][5]7,8,10,11,13,14,16,17,33 except that the F3L1 apoA1 analogue (1 µg per well) was used as coating antigen instead of fully delipidated and native apoA1. 20 The seropositivity cut-off for anti-cter apoA1 IgGs was prospectively set at an optical density (405 nm) value of 0.5, Figure 3.…”
Section: Blood Sampling Biomarkers Anti-apoa1 Igg and Anti-cter Apomentioning
confidence: 99%
See 2 more Smart Citations